Out‐of‐Pocket Costs for Transcranial Doppler Screening Among Privately Insured Children with Sickle Cell Anemia. (20th August 2020) - Reeves, S.; Ng, S.; Dombkowski, K.; Raphael, J.; Chua, K.‐P.
Abstract : National guidelines recommend that children 2‐16 years old with sickle cell anemia (SCA) receive annual transcranial Doppler (TCD) screening to assess stroke risk. It is unknown whether cost‐sharing deters receipt of TCD screening for privately insured children with SCA, particularly among those enrolled in high‐deductible health plans (HDHPs). Therefore, our objectives were to: (1) estimate out‐of‐pocket spending for TCD screening among privately insured children with SCA; and (2) assess whether TCD screening rates differ by HDHP enrollment status. This study utilized the 2009‐2017 IBM ® MarketScan ® Commercial Database, a national sample of claims from individuals with employer‐sponsored coverage. The study population included children 2‐16 years old with SCA that were enrolled for ≥ 1 calendar year of the study period. Outcomes were the proportion of children with ≥ 1 claim in a calendar year containing a procedure code for TCD and out‐of‐pocket spending per TCD claim; out‐of‐pocket spending was then stratified by HDHP enrollment status (yes/no). Logistic regression with generalized estimating equations was used to model the receipt of ≥ 1 TCD screen during a calendar year as predicted by HDHP enrollment, controlling for demographics and year. Children 2‐16 years old with SCA as identified through validated claims definitions. The study population consisted of 2, 519 children accounting for 7, 197 person‐years of enrollment. Mean age was 9.2 (SD 3.6) years; 50% were female; and 14% were HDHP enrollees. The proportion of children with ≥ 1 TCD claim during the year ranged from 40% to 44%. Out‐of‐pocket spending per TCD claim ranged from 0 to 1, 808 (median: 20, 25th‐75th percentile: 0‐111), exceeded 0 for 61% of TCD claims, and exceeded 100 for 27% of TCD claims. Out‐of‐pocket spending per TCD claim was higher for HDHP enrollees (median: 65, 25th‐75th percentile: 0‐252) compared to non‐HDHP enrollees (median: 18, 25th‐75th percentile: 0‐98). Out‐of‐pocket spending exceeded 100 for 42% of HDHP enrollees and 25% for non‐HDHP enrollees. HDHP enrollment was not associated with receipt of TCD screening (aOR: 1.06; 95% CI: 0.90, 1.25). Among privately insured children with SCA, less than half received recommended TCD screening. HDHP enrollment was not associated with TCD screening; however, 4 in 10 HDHP enrollees had out‐of‐pocket spending exceeding 100. Private health plans should consider eliminating cost‐sharing to ensure families are not unduly burdened by the costs of TCD screening. Departmental Funding.